Association of cartilage metabolism biomarkers and 25(OH)D levels with muscle biomechanical functions in professional rowers and canoeists - Małgorzata Ogurkowska; Tomasz Podgórski; Alicja Nowak (Scientific Reports, 2024)
Abstract The purpose of the study was to assess the association of cartilage metabolism biomarkers and vitamin D metabolite levels with muscle biomechanical functions in professional rowers and canoeists. The serum levels of aggrecan, cartilage oligomeric matrix protein (COMP), and 25-hydroxyvitamin D (25(OH)D) were determined in elite male sweep-oar rowers (n = 24) and canoeists (n = 15). This was followed by a biomechanical study consisting in isometric measurement of peak torque (PT) of muscles involved in the rowing cycle in the athletes. There were found significant correlations of COMP with the ratio of trunk PT flexor to extensor (p < 0.05) and 25(OH)D with trunk PT—left rotators (p < 0.05), knee joints PT—left and right flexor (p ≤ 0.01), ratio of knee joint PT—right flexor to knee joint PT—right extensor (p < 0.05) in rowers and aggreccan with elbow joint PT of the right flexor (p ≤ 0.01) and extensor (p = 0.05) in canoeists. The correlations of COMP and aggrecan levels with PT of the muscle groups studied in rowers and canoeists indicate the importance of stabilizing the muscular system in cartilage metabolism. The relationship between 25(OH)D status and biomechanical parameters confirm that vitamin D plays an important role in maintaining skeletal muscle health.